Methoxycarbazolyl-disubstituted dibenzofuranes as holes- and electrons-transporting hosts for phosphorescent and TADF-based OLEDs. (January 2020) - Bucinskas, Audrius; Bezvikonnyi, Oleksandr; Gudeika, Dalius; Volyniuk, Dmytro; Grazulevicius, Juozas V.
Abstract: In the search of universal host materials for organic light emitting diodes a new series of bipolar host materials containing methoxy-substituted carbazoles as the electron-donating and dibenzofuran as an electron-accepting units were designed and synthesized. Different linking topologies and number of methoxy groups attached to carbazolyl moiety were used to understand the impact of the strength of the donor moiety on the thermal, optical, photophysical, electrochemical and electroluminescent properties. The synthesized compounds exhibited relatively high thermal stability with 5% weight loss temperatures exceeding 378 °C and formed molecular glasses with high glass-transition temperatures ranging from 120 to 148 °C. High triplet energy values of 2.86–2.96 eV were estimated for dilute THF solutions at 77K. Hole and electron drift mobilities estimated using time-of-flight technique in solid layers approached 10 −4 cm 2 V −1 s −1  at high electric fields exceeding 3.6 × 10 5  V cm −1 . The synthesized methoxy-carbazole based compounds were tested as hosts in electrophosphorescent and TADF organic light-emitting diodes reaching luminance of 53000 cd m −2 and external quantum efficiency of 12.5%, in the best case. Graphical abstract: Image 1 Highlights: Derivatives of methoxy-substituted carbazoles and dibenzofuran were synthesized. Hole and electron drift mobilities approached 10 −4 cm 2 V −1 s −1 . The compounds were used as versatile host materials in phosphorescent and TADF OLEDs. OLED showed luminance of 53000 cd m −2 and external quantum efficiency of 12.5%.